2019
DOI: 10.4049/jimmunol.1801609
|View full text |Cite
|
Sign up to set email alerts
|

TCR Affinity Biases Th Cell Differentiation by Regulating CD25, Eef1e1, and Gbp2

Abstract: Naive CD4 + T lymphocytes differentiate into various Th cell subsets following TCR binding to microbial peptide:MHC class II (p:MHCII) complexes on dendritic cells (DCs). The affinity of the TCR interaction with p:MHCII plays a role in Th differentiation by mechanisms that are not completely understood. We found that low-affinity TCRs biased mouse naive T cells to become T follicular helper (Tfh) cells, whereas higher-affinity TCRs promoted the formation of Th1 or Th17 cells. We explored the basis for this phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…Although earlier reports suggested that Tfh cell differentiation requires high TCR signal strength, recent work supports the idea that Tfh cells develop across a wide range of signal strengths, while increasing TCR signal intensity favors Th1 generation (4)(5)(6)(7)(8)(9)(10)(11). A central difficulty in reconciling these findings is the use of different TCR tg systems as well as immunization and infection models that may induce distinct levels of costimulatory and inflammatory signals known to influence T cell differentiation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although earlier reports suggested that Tfh cell differentiation requires high TCR signal strength, recent work supports the idea that Tfh cells develop across a wide range of signal strengths, while increasing TCR signal intensity favors Th1 generation (4)(5)(6)(7)(8)(9)(10)(11). A central difficulty in reconciling these findings is the use of different TCR tg systems as well as immunization and infection models that may induce distinct levels of costimulatory and inflammatory signals known to influence T cell differentiation.…”
Section: Introductionmentioning
confidence: 90%
“…and Tfh cell fates is controversial (4)(5)(6)(7)(8)(9)(10)(11)(12). An essential role for TCR signal was implicated in a study assessing the phenotype of progeny derived from individual, TCR transgenic (tg) T cells responding during infection (9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MHCII gene polymorphism has been implicated in establishing or breaking central and peripheral tolerance for Th cells via fine tuning the affinity of pMHCII: TCR interactions and the TCR signal intensity ( Fig. 6c, d, e) [62][63][64][65][66][67][68]. Therefore, MHCII gene polymorphism is associated with the susceptibility or resistance to Th cell-mediated autoimmunity.…”
Section: Clinical Evidencesmentioning
confidence: 99%
“…Were this not so, there wouldn't even be ineffective T cell responses to nonself epitopes since at least one of out of many heterogeneous T helper cell responses (Th 1 , Th 2 , Th 17 , Th 22 , Th 9 , etc) would be effective. Moreover, both ineffective T helper responses to nonself and their control by thymic Tregs must be epitope-specific (Usharauli and Kamala, 2018;DiToro et al, 2018;Kotov et al, 2019;Akkaya et al, 2019). In contrast, ineffective, polarizing T helpers must cross-inhibit other types of T helper differentiation in an epitope non-specific manner (otherwise, again, there would not be an ineffective T helper response to begin with).…”
Section: Pathological T Helper Polarization Is Initiated At the Tcr/ementioning
confidence: 99%